A Rich Model for Moving Image Databases - Turner, James M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper is related to the conference theme of Technologies. It discusses how new theories of information organisation developed from the results of recent research into moving image organisation point to the need for better information systems to manage the rich information that is available but which is underused. Specifically, an information system is proposed which offers access using text, images or sound. XML is proposed as...